Students’ Tendency in Using Fillers in Situations of Randomly Appointed to Answer Oral Questions - Meylana, Ardhy; Fitriati, Sri Wuli; Alif, Wening Nur Habibah (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
For EFL learners, fillers can easily be found in conversation, especially in a spontaneous situation. Mostly, EFL learners found difficulty in expressing their idea by words, so they produced a sound such as “ehm”, or repeated their words and sometimes containing pauses which are called fillers. Fillers can indicate that the interlocutor is not competent, but on the other hand, they can be used as a strategy to create conversation. Although fillers are categorized as strategic competence, they have several functions to make conversation smooth; overproducing will make it challenging for the interlocutor to catch the meaning. The research focuses on fillers and parts produced by an English class of senior high school students in Semarang. Research in senior high school is necessary because high school is the final level in the nine years of compulsory education launched in Indonesia. So, the output of high school graduates will represent the majority of the ability of Indonesian English skills. Researchers took the data in the classroom by pointing students randomly to answer some questions to investigate the use of fillers and to analyze their functions. The data was collected by using audio recording and transcribing. This research belongs to a descriptive qualitative study. Rose’s (1998) theory is used in this study to reveal the types of fillers. To analyze the fillers function that students used, researchers will use the theory from Stenstrom (1994). The expected result of this research is that this can be an analytical material for educators in Indonesia to improve students’ abilities, especially in conversation.